2013
DOI: 10.5032/jae.2013.03100
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Use of Experiential Learning Strategies in Agricultural Laboratories

Abstract: Experiential learning in agricultural laboratories has been a foundational component of secondary agricultural education. While inclusion of the four stages of the experiential learning cycle can enhance student learning in laboratory settings to help students reach various goals related to scientific literacy and higher-level thinking, agricultural laboratories have traditionally been sites of psychomotor skill development. This exploratory study used a nonexperimental survey design to assess NAAE members' us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…While utilizing experiential learning experiences, agricultural educators rarely provide opportunities for active experimentation or internal reflection (Osborne, 1994). In a study by Shoulders and Myers (2013), the most commonly omitted stage of experiential learning was active experimentation. The statement "learning by doing" is commonly utilized within agricultural education (Phipps et al, 2008), however, that practice only uses part of the experiential learning theory as it places the entire focus on concrete experiences, rather than on the holistic process of experiential learning, which should also include reflection and active experimentation (Clark et al, 2010).…”
Section: Frameworkmentioning
confidence: 99%
“…While utilizing experiential learning experiences, agricultural educators rarely provide opportunities for active experimentation or internal reflection (Osborne, 1994). In a study by Shoulders and Myers (2013), the most commonly omitted stage of experiential learning was active experimentation. The statement "learning by doing" is commonly utilized within agricultural education (Phipps et al, 2008), however, that practice only uses part of the experiential learning theory as it places the entire focus on concrete experiences, rather than on the holistic process of experiential learning, which should also include reflection and active experimentation (Clark et al, 2010).…”
Section: Frameworkmentioning
confidence: 99%
“…"Due to the increasing gap between the general public and production agriculture there is an increasing need for agricultural education taught utilizing the experiential learning theory" (Gilbert, 2013, p. vi). Agricultural education teachers have utilized laboratories as a means to facilitate Supervised Agriculture Experience (SAE) programs and experiential teaching and learning since the inception of the Smith-Hughes Act of 1917 (Croom, 2008;Shoulders & Myers, 2013). It has been recommended teacher preparation and in-service teacher programs reconsider the breadth and depth of SAE and experiential learning education (Retallick, 2010;Shoulders & Myers, 2012).…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…Many agriscience teachers have been unaware of the experiential learning cycle and have needed instruction to develop curricular plans (Arnold, Warner, & Osborne, 2006;Shoulders & Myers, 2013) which would guide students through a series of four cyclical events that include a concrete experience, reflective observation, abstract conceptualization, and active experimentation (Kolb, 1984;Roberts, 2006). Typically, formal experiential learning behaviors arise in classrooms and laboratories (Etling, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As education has been reformed, the role of the teacher has changed from delivering information in a passive teacher-centered environment to facilitating learning in an active studentcentered environment (Padron & Waxman, 1999). Research has indicated that teacher knowledge of the experiential learning cycle and how people learn has become increasingly important to assess what was learned (Arnold et al, 2006;Baker et al, 2014;Knobloch, 2003;Shoulders & Myers, 2013). Baker, Robinson, and Kolb (2012) suggested the need to compare students who are engaged in a series of agricultural education experiences to those who experience similar concepts delivered in a lecture-based approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation